Naturally enriched 13C breath test as a carbohydrate intake marker in obese women - Beato, Gabriel Cunha [UNESP]; Ravelli, Michele Novaes; Sartori, Maria Márcia Pereira [UNESP]; de Oliveira, Maria Rita Marques [UNESP] (Springer Nature, 2020)
Background: The 13C breath test has been proposed as a potential biomarker for the evaluation of metabolism and carbohydrate intake. To study the dynamics of the use of substrates in human metabolism is especially important for glucose metabolism in obese people. Purpose: This study aimed to verify the use of 13C in a naturally enriched corn glucose liquid meal through the breath test as a potential marker of energy metabolism in women with a body mass index (BMI) above 35 kg /m2. Methods: Twenty-five woman (13 non-obese; 12 obese) participated in the study. The breath samples were collected in tubes prior to consumption of the standard liquid meal and at 30-min intervals for 6 h and analyzed in a continuous flow isotope ratio mass spectrometer. The curves of breath isotopic enrichment were adjusted by the Boltzmann sigmoidal regression model, and the t test was used to evaluate differences between the means of the curves. Results: It was found a faster metabolic turn-over of the 13C-glucose in obese women. Conclusion: The breath test using naturally enriched stable isotopes has potential to be used as an energy metabolism marker in subjects with different BMI.
Keywords: 13C-glucose; Biomarker; Breath test; Glucose metabolism; Stable isotopes